The influence of latent toxoplasmosis on women's reproductive function: four cross-sectional studies - Kankova, Sarka; Flegr, Jaroslav; Calda, Pavel (Folia parasitologica, 2015)
Several studies have investigated the association between infection with Toxoplasma gondii (Nicolle et Manceaux, 1908), pregnancy and fertility, but the results of studies focused on the fertility are rather ambiguous. Here we report results of four new cross-sectional studies. The studies were performed in the General University Hospital, Prague (study A with n = 1 165, and study C with n = 317), in private clinics of the Centre of Reproductive Medicine, Prague (study B with n = 1 016), and in a population of Czech and Slovak volunteers from the Facebook page 'Guinea Pigs' willing to participate in various basic science studies (study D with n = 524). In studies A and B, the clinical records were used to assess the fertility problems, whereas in studies C and D, the women were asked to rate their fertility problems using a six-point scale. Pregnant T. gondii-infected women were older than T. gondii-free women (study A: 33.1 vs 31.2, P < 0.001; study B: 30.6 vs 29.6, P = 0.012) and more often used assisted reproductive technology to conceive (study A: 17.2% vs 12.4%, P = 0.041; study B: 13.4% vs 9.2%, P = 0.317). Pregnant T. gondii-infected primiparous women were older than T. gondii-free primiparas (study A: 31.1 vs 29.5, P < 0.001; study B: 29.7 vs 28.9, P = 0.064) and more often used assisted reproductive technology to conceive (study A: 24.7% vs 14.4%, P = 0.010; study B: 15.9% vs 15.5%, P = 0.888). T. gondii-infected women reported to take a longer time to conceive than T. gondii-free women (P = 0.015). They also claimed to have more fertility problems than T. gondii-free women (P < 0.0001). Our results suggest that 'asymptomatic' latent toxoplasmosis could be a more serious source of fertility problems and health-associated burden than more severe but far rarer congenital toxoplasmosis.